Maqasid-based protection assessment model for user generated content / Sharifah Aliman - Aliman, Sharifah (Institute of Graduate Studies, UiTM, 2017)
Social media applications allow users to not only generate their own content (user-generated content(UGC)) but also to share with other social media users. Due to the dynamics and real-time publications of social media, many social media users lack the ability to think deeply or to acknowledge the negative impacts of their content that could harm on themselves or others in similar situations. The purpose of this research is to investigate how social media users protect themselves and others whilst using various social media. Literature shows that the disseminated food-based UGC without a filtering phase as this may contain disinformation and misinformation that can lead to such risks as false rumours, deception, panic situations, loss of credibility and a loss of reputation. In contrast to Western humanistic theories, Islamic principles offers an integral spiritual facet on protection measures that may serve as a form of self-awareness and self-assessment instrument for social media users and their online activities. Thus, this study proposes a new protection assessment model based on the Maqasid Al-Shariah framework...